2014
DOI: 10.1093/ejcts/ezu201
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions, diagnostic challenges and treatment opportunities in bioprosthetic valve thrombosis: lessons from a case series

Abstract: BPVT may occur late after surgical implantation. VKA therapy resulted in haemodynamic and clinical improvement with minimal risk, and should be considered the first-line therapy in haemodynamically stable patients. Echocardiographic criteria for improving BPVT diagnosis are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 22 publications
0
58
0
3
Order By: Relevance
“…Previously reported cases of early valve thrombosis after AVR, excluding patients on anticoagulation or thrombolytic therapy, 6-8 are summarized in Table 1. 3,5,[9][10][11][12][13][14][15][16][17][18][19][20] Porcine aortic valves were used in all but 2 patients, in whom a pericardial valve was used. 9, 15 Brown and colleagues 5 reported no thrombosis cases in stented pericardial valves or stentless porcine valves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously reported cases of early valve thrombosis after AVR, excluding patients on anticoagulation or thrombolytic therapy, 6-8 are summarized in Table 1. 3,5,[9][10][11][12][13][14][15][16][17][18][19][20] Porcine aortic valves were used in all but 2 patients, in whom a pericardial valve was used. 9, 15 Brown and colleagues 5 reported no thrombosis cases in stented pericardial valves or stentless porcine valves.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The largest study on bioprosthetic valve thrombosis reported a peak incidence 13 to 24 months after surgical implantation. 20 The literature review found that approximately half of the cases occurred after 13 months.…”
Section: Discussionmentioning
confidence: 99%
“…The most important cause of prosthetic valve thrombosis is inadequate anticoagulation, which is more common with mechanical valves, but thrombosis can occur with bioprostheses long after implantation [23,26,27].…”
Section: Thrombosis and Pannus Formationmentioning
confidence: 99%
“…17 Thrombosis of bioprosthetic valves is increasingly recognized as a cause of obstruction, and findings at echocardiography that suggest thrombosis have been proposed. 4,18 MDCT seems promising for evaluation of cases of suspected thrombosis of bioprosthetic valves 19 because image quality is generally good with fewer artifacts. Comparison of these modalities is an appropriate area for future study.…”
Section: See Article By Gündüz Et Almentioning
confidence: 99%
“…2,3 However, it can occur with bioprostheses and may develop long after implantation. 4 Pannus is a more chronic process associated with ingrowth of tissue, causing obstruction. 5 Distinguishing between thrombus and pannus as a cause of obstruction is important because thrombus can potentially be treated with fibrinolysis, whereas pannus requires surgical intervention to relieve the obstruction.…”
mentioning
confidence: 99%